UNIVERSITY NOTES. (The Accounting Review, 1926)
Abstract This article announces news from different universities and colleges of the U.S. as of June 1926. The courses in hotel management now being offered in the College of Home Economics include two required courses in hotel accounting and the general elementary accounting, from the Cornell University. Announcement has been received that a "System of Lessons of Accounting," by Professor C. Panayotopoulo, has Just been published. Darmouth College announces that Mr. Archie M. Peiseb, in charge of the accounting courses in the Amos Puck School of Business Administration and Finance, has been recently admitted to membership in the American Institute of Accountants. The following members of last year's staff have left the Institution, M. Watters, professor of commerce; Braddock, instructor in advertising; J. B. Hosmer, instructor in journalism; William T. Ward, associate in advertising from Georgia Institute of Technology. Mr. Rollin C. Bill is completing b's work for an M. B. A. at Harvard, specializing in accounting at University of California .